Penerapan cost volume profit sebagai dasar perencanaan penjualan untuk laba yang diharapkan PT. Sumber Trijaya Lestari Cabang Tomohon - Rellam, Dian Natalia Erwinda; Mawikere, Lidia M.; Tangkuman, Steven Josia (Manajemen Bisnis dan Keuangan Korporat, 2025)
CVP is a tool that can help companies in decision making so that companies can find out to what extent the company achieves its profit or benefit in determining sales volume. This study aims to determine profit and sales planning using CVP at PT. Sumber Trijaya Lestari Tomohon Branch. The type of research used is qualitative with a descriptive qualitative approach. The type of data used is primary and secondary data with data collection, namely interviews and documentation. The results of the study showed that during the company's sales in one period, the company experienced fluctuations at the beginning of the period, while in the following month the company obtained an increase in sales volume so that from the calculations obtained, the company can be at the break-even point and the safe limit level of sales.